2022
DOI: 10.1007/s10803-022-05800-y
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Caregivers Remotely During a Pandemic: Comparison of WHO Caregiver Skills Training Delivered Online Versus in Person in Public Health Settings in Italy

Abstract: Feasibility, acceptability and effectiveness data of a virtual adaptation of the WHO Caregiver Skills Training (CST; n = 25) were compared with those of a pilot RCT of CST delivered in person (n = 43) against treatment as usual (TAU; n = 43). Virtual CST was delivered with high levels of integrity, but received lower ratings in some caregiver- and facilitator-rated acceptability and feasibility dimensions. Qualitative analysis identified both benefits (flexibility, convenience, clinical usefulness) and challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
1
4
0
Order By: Relevance
“…Finally, although some studies have reported high levels of acceptability related to telehealth-based caregiver interventions (Pickard et al, 2016;Sengupta et al, 2021), in this current study, reported perceptions of satisfaction and knowledge gained were lower for participants of virtually-held classes regardless of class topic or instructor. This finding is consistent with lower levels of acceptability found in another recent caregiver education study deliver virtual services, but in this case direct intervention (Ferrante et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, although some studies have reported high levels of acceptability related to telehealth-based caregiver interventions (Pickard et al, 2016;Sengupta et al, 2021), in this current study, reported perceptions of satisfaction and knowledge gained were lower for participants of virtually-held classes regardless of class topic or instructor. This finding is consistent with lower levels of acceptability found in another recent caregiver education study deliver virtual services, but in this case direct intervention (Ferrante et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…There is an abundance of research on the efficacy of group‐based and individualized parent training interventions for ASD and I/DD (Bearss et al, 2015; Ferrante et al, 2022; Machalicek et al, 2015; Neece & Lima, 2016; O'Donovan et al, 2019; Ragni et al, 2022). However, in the absence of or while waiting for therapeutic interventions, caregiver education classes are one mode of reaching families to provide general, supportive guidance and strategies on topics related to I/DD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the study demonstrate that an acceptable, feasible, open access caregiver‐mediated intervention implemented in the community can lead to a sustained improvement in the quality of the caregiver–child dyadic interaction through enhancing caregiver's skills supportive of such interaction. The WHO CST has been shown to be feasible and acceptable across both low‐and‐middle‐income countries (Montiel‐Nava et al, 2022; Sengupta et al, 2021; Tekola et al, 2020) and high‐income countries (Ferrante et al, 2022; Lau et al, 2022; Salomone, Ferrante, et al, 2021; Seng et al, 2022), with evidence of treatment effects on caregiver skills and overall quality of the dyadic interaction (Salomone, Settanni, et al, 2021). The current study shows that it is precisely this improvement of caregiver skills that in turn can promote social communication outcomes in the child.…”
Section: Discussionmentioning
confidence: 99%
“…Nevill et al (2018) reports that when group-based formats were used, group size was typically small with four-five parents per group. However, some recent studies have also included larger group sizes of eight to 10 parents (e.g., Ferrante et al, 2022;Li et al, 2022).…”
Section: Pms Delivery Approachesmentioning
confidence: 99%